Circadian skin temperature rhythms, circadian activity rhythms and sleep in individuals with self-reported depressive symptoms. (October 2019) - Lorenz, Noah; Spada, Janek; Sander, Christian; Riedel-Heller, Steffie G.; Hegerl, Ulrich
Abstract: Background: Disturbed circadian rhythms have been associated with depression. New body-worn devices allow the objective recording of circadian parameters such as physical activity, skin temperature and sleep. The objective of this study was to investigate whether circadian skin temperature and circadian activity rhythms are altered in depressed individuals. Methods: Data on skin temperature, physical activity and sleep were available for 1610 subjects from a population-based cohort study. In a matching process two groups were formed for analysis: 121 participants with pronounced depression symptoms (CES-D Score > 21) and n = 121 matched non-depressed controls (CES-D Score < 15). Circadian rhythms were investigated by analyzing non-parametric rhythm indicators of 24-h skin temperature and physical activity data. Sleep timing, continuity and quantity were calculated from actigraphy. Results: No differences between the groups were found when all participants were considered. After excluding antidepressant medicated participants, the depression group was found to have a lower skin temperature amplitude t(208) = 2.45, p = .015 and a less stable skin temperature rhythm t(208) = 2.40, p = .017. The amplitude predicted the group status (beta = −5.529, p = .016). No effects were found for activity or sleep. Conclusion: The results indicate that skin-temperature rhythms are blunted in unmedicated depressed individuals. This could be a promising non-invasive marker for further analysis.